Benefit of forest conservation on river water quality - Othman, D. (Forestry Department Peninsular Malaysia, 2014)
The study was carried out in several selected forests catchments namely Wang Kelian, Endau, Rompin, Gunung Jerai, Stong, Gunung Mandi Angin, Ulu Muda, Taman rimba Kenong and Coupe 1999. All the selected forest catchments are considered as conservation forest except Coupe 1999 in Sabah. Coupe 1999 was under active logging without proper conservation procedure. The sampling locations were established in the middle section of the river for collecting watersamples. The water sample was collected at 60% of the total depth from the river bed. Nine water quality parameters were analyzedPh, electrical conductivity, turbidity, dissolved oxygen, temperature, suspended solids, biochemical oxygen demand, chemical oxygen demand and ammoniacal-nitrogen. The data collected in the field were compared to the Malaysian Interim National Water Quality Standards for water quality status assessment. The results showed that the conservation of forest catchments play an important in maintaning the sustainability of water resource in terms of water quality and majority of the rivers fall under Class 1 Except for rivers found in Coupe 1999.